Evaluation of the Role of MSCT in the Diagnosis of Ureteral Kidney Stones - Dinh Au, Hoang; Van Ngoc, Doan (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2023)
A study of 100 patients with ureteral kidney stones, in which 66 cases of kidney stones and 68 cases of ureteral stones were taken with 128 slices of computerized tomography at Hanoi Medical University Hospital from September 2019 to the end of January 2020. Results: male/female ratio was 1.7/1. The mean age was 51.2 ± 11.7. The rate of renal function decline (creatinine increase) was 18%. The supersonic, X-ray, and Multi-slice Computer Tomography (MSCT) detected stones in 89%, 84%, and 100% of cases, respectively, including 32% of kidney stones, 34% of ureteral stones, 34% of stones in both kidneys and ureters, 63.6% kidney stones in many positions. Patients with two or more stones accounted for 78.8% and the average kidney stone size was 15.5 ± 10.9 mm. Ureteral stones in the upper third accounted for 54.4%, one stone accounted for 77.9%, and the average size of ureteral stones was 9.1 ± 3.6 mm. Complications of nephrolithiasis caused by stones account for 82%, and grades II and III are the most common. Complications of ureteral dilatation due to stones accounted for 51%, perirenal fat infiltration accounted for 24% and 32% of cases of drug excretion lasted more than 1 hour. Conclusion: MSCT plays an important role in diagnosing urinary stones and assessing renal function before treatment.